Broadband Passively Mode-Locked Fiber Laser with DNA Aqueous Solution as Saturable Absorber - Mijin Kim (MDPI AG, 2021)
We demonstrate a passively mode-locked fiber laser using aqueous DNA solution as a saturable absorber (SA), with broadband pulse laser emission from 1 to 1.5 µm. The mode-locked laser with erbium-doped fiber as the gain material has a center wavelength of 1563 nm, a 3 dB bandwidth of 3.9 nm, and a pulse width of 822 fs, whereas the laser with ytterbium-doped fiber as the gain material and an identical DNA aqueous SA has a center wavelength of 1037 nm, a 3 dB bandwidth of 5.04 nm, and a pulse width of 250 ps. The proposed laser, which is simple and cost effective to fabricate, exhibits excellent long-term stability as well as thermal stability during high-power operation. This mode-locked laser scheme with a liquid-phase DNA component has the potential to provide in-depth understanding of the optical nonlinearity and usefulness of DNA.